Overhead line and underground cable transmission infrastructure project: Questionnaire instruments - Ashworth, Peta; Ackermann, Fran; Cetois, Audrey (Curtin University, 2023)
These pre- and post- surveys investigate the publics attitudes to transmission infrastructure with a focus on comparing overhead lines with underground cables with an aim to understand the factors influencing individual acceptance of the transmission type.